Postpyloric nutrition to prevent emergencies – a step away from repeat inpatient care in children with methylmalonic acidaemia and propionic acidaemia – a case report of four cases - Schumann, Stefan; Rommel, Frank Risto; Cantez, Serdar; Alexanidou, Evdokia; Kamrath, Clemens; de Laffolie, Jan (Frontiers in Pediatrics, 2023)
Methylmalonic acidaemia (MMA) and propionic acidaemia (PA) are very rare autosomal recessive inherited metabolic diseases from the group of organoacidopathies. Katabolism due to minor infections can lead to metabolic decompensation including hyperammonemia and ketoacidosis, especially in small children. We present data from a small cohort to clarify whether placement of a percutaneous endoscopic gastrostomy with jejunal tube (J-PEG) reduce metabolic imbalances and hospital stays. The aim is to prevent emergencies from occurring by preventing metabolic derailments at an early stage. 4 patients with MMA (N = 3) or PA (N = 1) were included. Data were collected at every investigation, in particular pH value, pCO2, bicarbonate, base excess, ammonia and lactate. Due to repeated metabolic derailments, a percutaneous endoscopic gastrostomy was placed for postpyloric nutrition. In conclusion, placement of a percutaneous endoscopic gastrostomy with postpyloric tube appears to reduce the rate of metabolic decompensations. In addition, hospital stays and especially the number of treatment days can be reduced. This method, especially the placement of a postpyloric tube could enable parents to prevent catabolism when vomiting begins by continuously feeding through the jejunal part, as a step to prevent a metabolic emergency from occurring.